2016
DOI: 10.1111/jocs.12860
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of driveline infections in patients with left ventricular assist devices

Abstract: Driveline relocation with use of omentum is a feasible and effective procedure in selected cases of chronic severe driveline infection. The risk for perioperative bleeding should be taken into consideration and carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Although we used our institution's algorithm for surgical treatment, other novel surgical techniques for managing infections in these patients have been described. Of note, Pieri et al reported a technique of translocation and omental wrapping for severe chronic driveline infections . Jacoby et al described flap coverage for treating exposed LVAD hardware and intractable LVAD infections .…”
Section: Discussionmentioning
confidence: 99%
“…Although we used our institution's algorithm for surgical treatment, other novel surgical techniques for managing infections in these patients have been described. Of note, Pieri et al reported a technique of translocation and omental wrapping for severe chronic driveline infections . Jacoby et al described flap coverage for treating exposed LVAD hardware and intractable LVAD infections .…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, repositioning of the driveline exit site and rectus flaps may not be feasible. Alternatively, pedicled omentum can be used for coverage . In the event of device endocarditis, device explantation may be necessary for source control.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the device remains exposed after debridement, coverage with well‐vascularized, healthy tissue is necessary for definitive infection management. We and others have described coverage options for exposed devices . Given its proximity to LVAD hardware and generous pedicle length, the rectus abdominis myocutaneous flap is the most commonly used flap for device coverage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, antibiotics and minor debridement procedures were used to manage minor driveline infections, whereas exchange and transplantation were used to manage severe or recurrent pump and pump pocket infections (5). In cases where operative debridement leaves a defect, closure can be done with rectus muscle or omental flaps (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%